Requirement of male-specific dosage compensation in Drosophila females-implications of early X chromosome gene expression. - Gladstein, N.; McKeon, M.N.; Horabin, J.I. (PLoS Genetics, 2010)
Dosage compensation equates between the sexes the gene dose of sex chromosomes that carry substantially different gene content. In Drosophila, the single male X chromosome is hypertranscribed by approximately two-fold to effect this correction. The key genes are male lethal and appear not to be required in females, or affect their viability. Here, we show these male lethals do in fact have a role in females, and they participate in the very process which will eventually shut down their function--female determination. We find the male dosage compensation complex is required for upregulating transcription of the sex determination master switch, Sex-lethal, an X-linked gene which is specifically activated in females in response to their two X chromosomes. The levels of some X-linked genes are also affected, and some of these genes are used in the process of counting the number of X chromosomes early in development. Our data suggest that before the female state is set, the ground state is male and female X chromosome expression is elevated. Females thus utilize the male dosage compensation process to amplify the signal which determines their fate.